Black women, writing, and identity : migrations of the subject - Boyce Davies, Carole (Routledge, 1994)
A superb study of black women's writing, taking our understanding of identity, location and representation to new levels. A major contribution to a range of related fields including feminist, cultural and postcolonial studies.